Pengaruh Likuiditas Dan Leverage Terhadap Agresivitas Pajak Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Sektor Properti Dan Real Estate Yang Terdaftar Di Bei Periode 2018-2021 - Islamitha Adinda Putri; Mulyadi Mulyadi; Panata Bangar Hasioan Sianipar (Akuntansi, 2023)
This study aims to test and analyze the effect of liquidity and leverage on tax aggressiveness and to test and analyze the effect of company size on moderating liquidity and leverage on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange. The variables used in this study are liquidity and leverage as independent variables, tax aggressiveness as the dependent variable and firm size as a moderating variable. This hypothesis was tested using descriptive statistical analysis, classical assumption test, multiple regression test and moderation, hypothesis testing, namely the analysis test r and t test. The results of this study indicate that partially liquidity has no effect on tax aggressiveness, leverage has an effect on tax aggressiveness, firm size cannot moderate the effect of liquidity on tax aggressiveness, and firm size can moderate the effect of leverage on tax aggressiveness.